Caso Paiol de Telha: uma história dos descendentes de negros escravizados frente à expropriação de terras em Guarapuava, PR - Sene, Roberto Revelino (2008)
This dissertation presents the Case Storeroom of Tile, looking for to contemplate on a history of the black’s descendants of enslaved front to the expropriation of lands in Guarapuava, PR. We discussed some of the arguments during the research on the processes of construction of identities and of social organization in the disputes for lands in the State of Paraná, in Guarapuava, also detaching the black's roll in the Brazilian society. We problematized the historical visions about the relationship existent among slaves and their lord, considering how these visions started composing the main ideas about the formation of the Brazilian people, as well as its influence in specific cases as the one of the Storeroom of Tile. Starting from this case, we tried, to present a history so called “the minorities” and how these minorities are treated in the dynamics of the social processes, focusing our study in the form how that group of descendants of enslaves of the interior of paraná molded their strategies of defense, survival and reply to the system, forming their own identity trying to insert in the local society. For the historical reconstruction of the Case Storeroom of Tile, we studied mainly a dossier prepared by the Pastoral Commission of the Earth, analyzing the speeches and the approaches used in it to justify the organization of a movement with juridical existence in order to claim the inherited and expropriated lands, the ‘Association Heleodoro Storeroom of Tile’, whose actions we tried to understand and to problematize, studying which are their inspiring sources related to the movements of afro-descendants, syndical and country workers without land demands. This research brings us to understand that the traditional families of Guarapuava created a net of power in order to isolate and expropriate blacks-descendants of having their lands. Today these lands are occupied by the “Cooperativa Agrária Mista de Entre Rios”, descendants of European immigrants, showing that some groups are considered by the elite of the local society as worthy of be landowners, in a context where the economical expropriation of afro-descendants people go trough ethnical questions and racial prejudices are deep-rooted in the regional history